Servitization and circular economy economic and legal challenges - Keirsbilck, Bert 1980-; Terryn, Evelyne 1974-; Eyckmans, Johan; Rousseau, Sandra; Voinot, Denis (Intersentia, 2023)
Have you ever thought of renting a washing machine or subscribing to a ventilation service? The transition from a linear to a more circular economy that uses less scarce raw materials and causes less negative environmental impact, entails new business models and a shift from buying products to using products ('servitization', 'access-based consumption'). This trend has a huge potential, also in economic terms, not the least in b2b markets. However, taking into account behavioral barriers, and in absence of a clear regulatory framework, users feel uncertain and hesitant to engage in new, circular product-service systems ('PSS'). This book compiles the academic papers presented at a two-day international and interdisciplinary conference held in Leuven on 21 and 22 April 2022. This conference was organized at KU Leuven by Consumer Competition Market, in cooperation with the Renson Chair for data-driven servitization in creating healthy spaces, with the support of the European Law Institute. This book identifies economic and behavioral drivers and barriers of servitization as well as the main legal challenges in the servitization process
Keywords: Circular economy; Economics; Économie circulaire; Économie politique; economics; Recht; Geschäftsmodell; Produkt; Nutzung; Kundenorientierung; Nachhaltigkeit; Dienstleistung